Analysis of multidrug resistant Klebsiella pneumoniae and Enterobacter aggalomerans isolates from under five children suffering from acute respiratory infections in Dhaka, Bangladesh. - Chowdhury, Samina Kabir (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2015.